Migrant domestic work in Chile and COVID-19. Bolivian caregivers on waste ground - Rico, María Nieves; Leiva-Gómez, Sandra (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2021)
Migrant domestic work is an alternative to the care crisis in many countries. However, paid domestic work has not been adequately relieved as a care provider agent, nor have public policies been designed to grant it sufficient protection and basic rights. The covid pandemic exposed such shortcomings, conceptualizing as a syndemic the interrelationships between the care crisis, the health crisis and poverty, which exacerbate the negative consequences of covid 19. Taking these elements as a basis and through in-depth interviews and review of documents, the text analyzes the case of Bolivian domestic workers in Chile who carry out a circular migration and their vulnerability, when they are stranded on waste ground on the Chilean-Bolivian border. The article ends with proposals for public care policies for migrant domestic workers, with a rights-based approach and from a gender perspective.